The impact of HIV/AIDS on education worldwide - Wiseman, Alexander W., 1968-; Glover, Ryan (International perspectives on education and society ;, 2012)
This volume of the International Perspectives on Education and Society series examines the relationship between HIV/AIDS and education worldwide. Much of the mystery surrounding HIV/AIDS and education lies in the fact that many factors contextualize their intersection. Many of the children who are at risk of not finishing school or have never had the chance to attend school live day-to-day in communities with high HIV/AIDS infection rates. To exacerbate the problem, in some countries the highest HIV/AIDS infection rates are in marginalized and extremely poor communities while in others it is within the most affluent communities. This volume examines how education supports, combats or reacts to HIV/AIDS awareness, prevention and impact worldwide as well as its impact on education systems and teaching forces. Given the context and prevalence of HIV/AIDS worldwide, this volume presents information, policy case studies, and empirical research for use by educators, policymakers, and organizations about the relationship between HIV/AIDS and education, including how HIV/AIDS has impacted education systems and the potential impact education has on HIV/AIDS.